Effect of geometrical size and number of core on bending behaviour of web-core sandwich structure - Nur Khaleeda, Romli (2023)
Laser-welded sandwich structure is a promising solution due to the high stiffness-to-weight ratio, which is typically applied in the structure of shipbuilding. According to engineering demands, bending of the sandwich structure is frequently raised in the shipbuilding industry due to heavy loads. However, structural improvement with variant geometries and number of cores have not been clearly studied. Therefore, a detailed study of the sandwich structure with the technology of joining, strong and lightweight material is required. The primary aim of this research study is to investigate the effect of geometrical size and core number on the three-point bending performance of a web-core laser-welded sandwich structure. A Web-core laser-welded sandwich structure was manufactured using galvanised steel. In addition, the sandwich structure was fabricated with different web plate thicknesses, spacing distances, and number of cores. Besides that, two types of web-core sandwich structure were fabricated; with foam and without foam. Polyvinyl chloride (PVC) foam was chosen to be installed in the web-core sandwich structure. Furthermore, a finite element analysis was modelled with strain-based ductility to predict the bending behaviour of the web-core sandwich structure by different spacing distances and core numbers. Nevertheless, data from the literature review was extracted due to limited experimental data and applied to formulate the constitutive material in the Abaqus/Standard model. A tensile test was conducted on galvanised steel specimen and found that yield stress was initiated at 324.522 MPa. Based on the observation, failure of the two types of sandwich structures were found to be similar, where bending was initiated due to the bending of the sandwich structure. Although bending was established in both types of sandwich structure, the discussion was stated in different ways. The failure of the web-core laser-welded sandwich structure without foam was due to no constraint acted at the end-sides to support the structure during the three-point bending loading. Moreover, PVC foam was substituted to increase rigidity and bending strength of the web-core laser-welded sandwich structure. The substitution of the PVC foam was increased up to 90% on the structural strength. The FEA-Imperfection result was validated in the experimental result, where good agreement was achieved, in which the percentage error of the comparison was about 5.834%. Owing to the comparison of bending performances in the three-point bending load, the effect of geometrical size and number of cores on the web-core laser welded sandwich structure was beneficial to increase bending strength, where energy absorption would also be higher. However, the strength of bending would reduce because of the common failures in the sandwich structure system, such as debonding due to interface bonding and welding joint problems. Besides that, the strength of the sandwich structure was affected by an increasing number of cores, where rigidity of the sandwich structure was increased and stronger. In addition, the effect of variant spacing distances was also studied, and it was found that the larger space distance and thicker web plate thickness would increase the stability and stiffness of the sandwich structure, respectively.